Analisis Laporan Keuangan Sebagai Alat untuk Menilai Kinerja Keuangan Perusahaan pada PT. Unilever Inonesia TBK Tahun 2020-2023 - Sifani Jannah; Dalizanolo Hulu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze financial statements as a tool to assess the financial performance of PT Unilever Indonesia Tbk for the period 2020–2023. Using a descriptive quantitative approach, this research calculates key financial ratios, including liquidity ratios (current ratio), solvency ratios (debt to equity ratio), activity ratios (total asset turnover), and profitability ratios (net profit margin). The results show that the current ratio experienced a declining trend from 66.09% in 2020 to 55.16% in 2023, reflecting a weakening ability of the company to meet its short-term liabilities. The debt to equity ratio increased from 315.90% in 2020 to 392.85% in 2023, indicating a high dependence on debt financing. Meanwhile, the total asset turnover improved from 315.90% in 2020 to 392.85% in 2023, suggesting better efficiency in utilizing assets to generate sales. However, the net profit margin declined from 16.42% in 2020 to 12.26% in 2023, signaling a decrease in the company's effectiveness in converting sales into net profit. Based on these findings, PT Unilever Indonesia Tbk is advised to enhance the management of current assets, strengthen its capital structure by reducing reliance on debt, and thoroughly evaluate cost control and marketing strategies to improve profitability and ensure business sustainability in the future.